Helminthosporium camelliae-sinensis sp. nov., a hyphomycete associated with dead twigs of Camellia sinensis in Sichuan, China - Chi, Mei-Feng; Liang, Xiang-Dong; Wu, Na; Dissanayake, Asha J.; Liu, Jian-Kui (Phytotaxa, 2025)
Saprobic hyphomycetes exhibit high diversity on decaying plant materials. During an investigation of fungi associated with tea (Camellia sinensis) in Sichuan Province, China, two hyphomycetous taxa were isolated from dead tea twigs. Morphological characteristics placed both taxa within the genus Helminthosporium, a polyphyletic group in the family Massarinaceae (Pleosporales). This genus is characterized by septate, erect conidiophores producing acro-pleurogenous, distoseptate conidia with a distinct ring-shaped scar at the base. Based on morphological comparison and multi-locus phylogenetic analyses of the ITS, LSU, SSU, rpb2, and tef1-α gene regions, one isolate was identified as a novel species, H. camelliae-sinensis sp. nov., while the other was confirmed as H. velutinum, representing a new host record on C. sinensis. Detailed morphological descriptions, illustrations and an updated phylogeny of Helminthosporium are provided to support the taxonomic placement and enriching the understanding of its species diversity.